NETWORK COMPETENCE AND FIRM PERFORMANCE: THE MEDIATING ROLE OF ENTREPRENEURIAL INNOVATIVENESS AMONG MALAYSIAN CHINESE ENTREPRENEURS OF WHOLESALE BUSINESSES - Sulaiman Sajilan,; Shehnaz Tehseen, (Asian Academy of Management Journal, 2019)
Entrepreneurial innovativeness has been considered as one of the crucial factors for any firm to achieve its superior performances. The aim of this paper is to analyse the mediating effect of entrepreneurial innovativeness in the relationship between network competence and firm performances including financial performance, non-financial performance, and business growth. Data were collected from 150 Malaysian Chinese wholesalers from the states of Selangor and Kuala Lumpur. Non-probability sampling technique was used to get the target respondents. PLS-SEM technique was used to analyse the data. The results revealed positive as well as significant mediating influence of entrepreneurial innovativeness in the relationship between network competence and firm performances. This study also provides future recommendations and managerial implications.